A Sharia-Compliant Digital Accounting Information System Model: Design, Implementation, and Implications for Islamic Financial Practices - Andi Riska Andreani Syafaruddin; Alimuddin; Syarifuddin (LP2M IAIN Palopo, 2026)
This study aims to develop a Sharia-Compliant Digital Accounting Information System (SCDAIS) model that integrates digital accounting technologies with Islamic accounting principles, Sharia governance, and ethical objectives. Using a qualitative approach grounded in the interpretive paradigm, the research adopts a multi-sited ethnographic orientation to explore how digital accounting systems are conceptualized and practiced across Islamic financial institutions, including Islamic banks, fintech platforms, zakat and waqf institutions, and regulatory environments. Data were collected through participant observation, in-depth interviews with 12–15 key informants, and document analysis, and analyzed using thematic analysis guided by thick description. The findings reveal that digital accounting systems in Islamic contexts operate as socio-technical and socio-religious constructs shaped by institutional values, technological capabilities, and interpretations of Sharia principles. Five core dimensions of SCDAIS were identified: digital infrastructure, accounting system core, Sharia compliance mechanisms, governance structures, and maqasid al-shariah-oriented outcomes. The study highlights that digital technologies are inherently value-neutral and require intentional embedding of Sharia principles within system architecture to ensure compliance. Furthermore, human interpretation remains essential in addressing complex financial practices that cannot be fully automated. The proposed SCDAIS model contributes to the literature by offering an integrative framework that bridges technology, accounting, and Islamic ethics. Practically, the findings provide guidance for developing ethical, transparent, and accountable digital accounting systems that support sustainable Islamic financial practices in the digital economy.